NUCLEAR-SPIN AND G-FACTOR FROM TIME-RESOLVED AND TIME INTEGRAL ONLINE NUCLEAR ORIENTATION EXPERIMENTS - Richards, P; Stone, N (1993)
Guiding principles in the design of time resolved on-line nuclear orientation experiments are described which, when used in conjunction with time integral on-line nuclear orientation, optimise the simultaneous determination of the oriented state spin and g-factor. © 1993 J.C. Baltzer AG, Science Publishers.